PENDEKATAN SIX SIGMA UNTUK MENGURANGI PRODUK CACAT PADA PRODUKSI BOTOL DI CV XYZ - Nuri Kartini (Spektrum Industri, 2019)
CV. XYZ is a company engaged in consumer goods. In the production process, this company is still experiencing many problems. One of the problems faced is that there are still many defective products produced. This study aims to identify the causes of defective products, and provide proposed suggestions to minimize the defective products. The method used in this study is Six Sigma. Six Sigma is a statistical concept that measures a process related to disability at level six sigma which is only 3.4 defects of a million opportunities. From the data and the results of observations with the Six Sigma approach, Critical to Quality that occurs includes dirty bottles, cracks, gaps, ruptures and rejects. Disability occurs in the washing process with a percentage of disability of 0.41% with a value of sigma 4.65. The results of this study indicate that the main causes of defects that occur in the bottle washing process are inaccurate checking of goods, lack of training for employees, less ergonomic work positions and work environment, also there still no SOPs in the production process.